THE INFLUENCE OF VARIOUS CONCENTRATION OF RED ROSES (ROSA DAMASCENA MILL) FLOWER EXTRACT TO ANTHOCYANIN COLOR STABILITY JELLY AS BIOLOGY LEARNING SOURCE - Ratna Wulandari; Moch. Agus Krisno Budiyanto; Lud Waluyo (JPBI (Jurnal Pendidikan Biologi Indonesia), 2016)
Red roses flower (Rosa damascena Mill) is plant which can be cultivated in Indonesia. Red roses flower have a natural pigment contain that anthocyanin which can be used as food coloring. The crown of roses flower contain an anthocyanin pigment that include to flavonoid and kind of sianidin anthocyanin which have a function as antioxidant or free radical preventing. Pigment as bioactive is important compound that useful for human health. The aim of this research is to know various concentration influence of red roses flower extract and to know effective concentration that the most influence to color stability of anthocyanin jelly. Research types with treatment, repetition, and control. The design of this research using completely randomized design (RAL), with 6 treatment (0%, 1%, 2%, 3%, 4%, and 5%) and repeated 4 times. Population of this research is jelly. Sample of this research is jelly which added by red roses flower extract. If the data result is have normality, that the data is analysed by Anava one-way test and continue with Duncan’s 5%. Result of this research shown that there was influence of various concentration of red roses flower extract to color stability of anthocyanin jelly. Result test for color stability, the most influence concentration for brightness is 4%, red color is 5%, and yellow color is 0%.